KEJUARAAN PERTANDINGAN BULUTANGKIS USIA MUDA SMA/SMK/MA SEKOTA MATARAM BEKERJASMAN DENGAN UNDIKM TAHUN 2020 - Soemardiawan Soemardiawan; Susi Yundarwati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
Badminton is a sport that imposes human rights in great demand by the community both as a daily sport and chosen to be a professional sport by many young Indonesians. It is proven by the large number of badminton athletes sprung up both at the regional and national level. All athletes involved in badminton have one goal, namely to make Indonesia famous in the world. With the slowness of the achievements of Indonesian athletes and to better maintain the competition of badminton achievements in the international arena, then we reletion dengan University Pendidikan Mandalika UNDIKMA intends to hold a Badminton Championship SMA / SMK / MA throughout kota mataram